Amazing Impact of E-Learning Education in Rural India - Eugene I. Pradeepkumar, J.; Panchanatham, N. (Prabandhan: Indian Journal of Management, 2011)
Learning should be fast, relevant and integrated into day-to-day work patterns. One way of doing this is through e-learning. The issues were involved in developing and implementing e-learning. The study was conducted to analyze the benefits of E-Learning among the Rural college students of Nagapattinam District in Tamil Nadu and to analyze whether Engineering and Arts & Science students of rural colleges use the E-Learning facilities.